Emissions of a Single Cylinder Diesel Engine Operating with Ethanol - Mamat, Rizalman; Abdullah, Nik Rosli; Tamaldin, Noreffendy (2010)
The conventional software of GT-Power is used to simulate a single cylinder diesel engine. The diesel engine is simulated to study the engine emission when the engine is operating with ethanol as alternative fuel. The simulation results were compared with the data from the diesel engine operating with mineral diesel The simulations are conducted at full load condition for the engine operating with ethanol and mineral diesel. It is found that the emission of diesel engine operating with ethanol is higher as compared to mineral diesel.